2013
DOI: 10.1371/journal.pone.0067714
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns Predict Individual Specialization in the Diet of Dolphin Gulls

Abstract: Many animals show some degree of individual specialization in foraging strategies and diet. This has profound ecological and evolutionary implications. For example, populations containing diverse individual foraging strategies will respond in different ways to changes in the environment, thus affecting the capacity of the populations to adapt to environmental changes and to diversify. However, patterns of individual specialization have been examined in few species. Likewise it is usually unknown whether specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…Individual specialization is known to be widespread across a diverse set of taxa (Bolnick et al 2003, Bell et al 2009, Ceia & Ramos 2015, including different seabird species and other marine predators (e.g. Vander Zanden et al 2010, Votier et al 2010, Masello et al 2013, Ceia & Ramos 2015, Tyson et al 2015, Towner et al 2016, Yurkowski et al 2016. In general, individual specialization may have a strong impact on ecological processes and population dynamics, and there is evidence that this mechanism may reduce intra-specific competition among individuals, increase individual foraging efficiency and improve breeding success (Pierotti & Annett 1991, Bolnick et al 2003, Woo et al 2008, Araújo et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Individual specialization is known to be widespread across a diverse set of taxa (Bolnick et al 2003, Bell et al 2009, Ceia & Ramos 2015, including different seabird species and other marine predators (e.g. Vander Zanden et al 2010, Votier et al 2010, Masello et al 2013, Ceia & Ramos 2015, Tyson et al 2015, Towner et al 2016, Yurkowski et al 2016. In general, individual specialization may have a strong impact on ecological processes and population dynamics, and there is evidence that this mechanism may reduce intra-specific competition among individuals, increase individual foraging efficiency and improve breeding success (Pierotti & Annett 1991, Bolnick et al 2003, Woo et al 2008, Araújo et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…These may provide gentoos greater resilience to buffer against changes in prey availability and fast changing environmental conditions, especially as their foraging range is usually limited (Lescroël & Bost 2005, Polito et al 2015. However, within this context, gentoos still exhibit individual specialisation, helping them reduce intra-specific competition and/or increasing their foraging efficiency (dit Durell 2000, Masello et al 2013). Dietary specialisations outside of a single breeding season were also highlighted, suggesting that gentoo penguins are type 'B' generalists.…”
Section: Discussionmentioning
confidence: 99%
“…When data on diet are not available, behavioural information (such as dive depths and the proportion of trips associated with fishing boats) or the use of areas where particular prey occur (proportion of time at each feeding site) have been used to assign individuals to different diet groups (e.g. Ropert-Coudert et al 2003, Montevecchi et al 2009, Masello et al 2013, Patrick et al 2015, Tyson et al 2015. The threshold used for separating specialists and generalists is often arbitrary.…”
Section: Diet Using Conventional Approachesmentioning
confidence: 99%
“…Indeed, if individuals specialise on different resources or environments over different seasons, studying specialisation over the whole year, for example, might prevent the detection of individual specialisation (although this issue can be dealt with by including the correct fixed effects). In the case of seabirds, although several studies have revealed that dietary and behavioural specialisations are widespread, it is unclear for how long these specialisations are maintained (Masello et al 2013, Patrick et al 2014; but see Wakefield et al 2015). It is likely, however, that repeatability in foraging behaviour declines at longer temporal scales because of temporal changes in the availability and predictability of resources (Woo et al 2008, Bell et al 2009, Ceia et al 2014.…”
Section: Controlling For Pseudo-repeatabilitymentioning
confidence: 99%
See 1 more Smart Citation